NOSOCOMIAL COVID-19 INFECTION IN A PEDIATRIC PATIENT WITH ACUTE LYMPHOBLASTIC LEUKEMIA: A CASE REPORT - PORTELA DE AZEVEDO, ARIMATÉIA; LIMA MICHILES, TAANY; PINTO DE OLIVEIRA, ADRIANA REGINA; SALLES ARRAES PEDROSA BARRETO, ANTÔNIO; ALVES DE PINHO , ALEX; DI LORENZO , CHRISTIANNI; COSTA DE JESUS, LUCAS; ARAGO CORDOVIL, ALCENIR; SILVA REIS, ERNESTINA; GÓIS FARIAS, MARLÚCIA (Brazilian Journal of Implantology and Health Sciences, 2024)
hospitalization and that manifests itself during hospitalization, or even after discharge, when it can be related to hospitalization or hospital procedures. Objective: To show, through a case study, a pediatric patient with acute lymphoblastic leukemia infected in an intra-hospital environment by the coronavirus. Methodology: Retrospective, descriptive study, case report type. Case study: Female patient, 04 years old, diagnosed with acute lymphoblastic leukemia presenting leukosis, signs of leukemic dysplasia and symptoms of extramedullary leukemic infiltration with hyperleukocytosis and mucositis. The patient presented Severe Acute Respiratory Syndrome, and an RT-PCR result indicated the presence of SARS-CoV-2 virus antigens in the analyzed sample, therefore, the infection was considered to be of intra-hospital (nosocomial) transmission. After receiving instructions, the patient and companion were transferred to a private room with standard precautions (droplet). In the following days, the patient showed significant improvement in her condition, with a calm facial expression, and normal skin and mucous membranes. She was discharged to continue medical monitoring at a center specializing in hematology and hemotherapy. Conclusion: PPE must be used in all activities in which it is not possible to eliminate the risk of disease transmission. Therefore, its use is a duty of the employee and its provision is an obligation of the employer.